THE EFFECT OF LIP PRESSURE IN PATIENTS WITH A DAMAGED CLEFT LIP AND PALATE - Sharopov, Sanjar; Tojiev, Feruz (Инновационные исследования в современном мире: теория и практика, 2023)
The question of congenital underdevelopment of the upper jaw in children with cleft upper lip and palate and its role in the occurrence and development of preoperative and postoperative deformities of the facial skeleton is widely discussed in the literature. The published works provide contradictory information, experts express contradictory opinions about the concept of "underdevelopment of the upper jaw" and the assessment of its role in the clinic of bone deformities in this group of patients.